2014
DOI: 10.2220/biomedres.35.193
|View full text |Cite
|
Sign up to set email alerts
|

Type II collagen peptide stimulates Akt leading to nuclear factor-κB activation: Its inhibition by hyaluronan

Abstract: While nuclear factor (NF)-κB is a critical pathway for matrix metalloproteinase (MMP)-13 induction in chondrocytes, intracellular upstream events for NF-κB activation by the type II collagen peptide (CB12-II) with catabolic activities remain unclear. Hyaluronan (HA) of high molecular weight is clinically used for treatment of osteoarthritis (OA) by intra-articular injection. Although HA can suppress NF-κB activation by CB12-II, it is still obscure how HA affects intracellular upstream pathways leading to NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Healthy articular chondrocytes are post-mitotic cells expected to survive for several years in a maturation arrested state which only requires a low homeostatic turnover of extracellular matrix (ECM) proteins. An intact ECM delivers survival signal to chondrocytes 1 while, conversely, proteolytic enzymes leads to production of bioactive molecules that promote chondrocyte differentiation, thus boosting osteoarthritis (OA) pathogenesis 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Healthy articular chondrocytes are post-mitotic cells expected to survive for several years in a maturation arrested state which only requires a low homeostatic turnover of extracellular matrix (ECM) proteins. An intact ECM delivers survival signal to chondrocytes 1 while, conversely, proteolytic enzymes leads to production of bioactive molecules that promote chondrocyte differentiation, thus boosting osteoarthritis (OA) pathogenesis 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that CD44 may regulate the expression of catabolic genes, including MMP and ADAMTS, through the NF-κB signalling pathway. 53 , 54 We considered that C-HA-DOs may affect the expression of a series of genes involved in OA by inhibiting CD44 expression through a similar mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Integrins, which are collagen receptors, lead to the activation of MAPK/ERK and PI3K/AKT signaling pathways when MSCs come into contact with the ECM [49]. Previous studies found that both collagen type I and type II can induce the activation of ERK and AKT [50][51][52]. Collagens also activate Smad signaling, which is involved in the crosstalk between MAPK/ERK and PI3K/AKT [53][54][55].…”
Section: Figmentioning
confidence: 99%